Sulfuric Activated Carbon of Black Cumin (Nigella sativa L.) Seeds for the Removal of Cadmium(II) and Methylene Blue Dye - Thabede, Patience Mapule; Shooto, Ntaote David; Xaba, Thokozani; Naidoo, Eliazer Bobby (Asian Journal of Chemistry, 2020)
Carbon from black cumin seeds was modified with 10 and 20% sulfuric acid to obtain the activated adsorbents. Pristine carbon from black cumin seeds, 10 and 20% H2SO4 activated carbon from black cumin seeds were labelled CBC, ACBC-10 and ACBC-20, respectively. The adsorbents were characterized by SEM, XRD, FTIR, TGA and BET. The adsorbents maximum trend for Cd(II) was ACBC-10 > ACBC-20 > CBC. The maximum capacity trend for methylene blue dye was ACBC-20 > ACBC-10 > CBC. The kinetic model best fitted pseudo second order for Cd(II) which gave r2 values of 0.991-0.998. The methylene blue fitted pseudo first order model with r2 values ranging from 0.993-0.997. Pseudo first order suggested that the adsorption mechanism for methylene blue onto adsorbents involved van der Waal forces of attraction. The equilibrium data fitted Langmuir isotherm model for CBC, ACBC-10 and ACBC-20 with r2 of 0.994 to 0.998 for the removal of methylene blue whilst the removal of Cd(II) followed Freundlich with r2 ranging from 0.992 to 0.997. This suggested that the different adsorption processes were involved between the adsorbate and the adsorbents. Gibb′s free energy (ΔGº) for Cd(II) and methylene blue onto CBC, ACBC-10 and ACBC-20 suggested that the reaction was spontaneous. The adsorption of Cd(II) and methylene blue was endothermic, positive values (ΔHº). This suggested that the enthalpy (ΔHº) had a weak interactive force process whose low energy is associated with electrostatic attraction.